2023
DOI: 10.1186/s12889-023-15045-8
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the relationship between breastfeeding and the incidence of infant illnesses in Ireland: evidence from a nationally representative prospective cohort study

Abstract: Background Ireland has one of the lowest BF rates in the world. This study investigates the association between breastfeeding and infant health in Ireland. Methods A cross-sectional, secondary analysis of data collected from Growing Up in Ireland (GUI): the National Longitudinal Study of Children was conducted. The average morbidity for 2212. infants exclusively breastfed for at least 90 days (EBF90days) was compared to data for 398… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…These data indicate that breastfeeding has not yet reached the optimal prevalence in the majority of the countries globally and as previously focused on, this poses a problem not only for the infants but also for the mother due to the many health benefits the mother can obtain from breastfeeding [26,27]. According to Victoria et al, 823,000 deaths in children younger than the age of 5 and up to 20,000 deaths from breast cancer can be prevented each year only by scaling up the level of breastfeeding to a nearuniversal level [30].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…These data indicate that breastfeeding has not yet reached the optimal prevalence in the majority of the countries globally and as previously focused on, this poses a problem not only for the infants but also for the mother due to the many health benefits the mother can obtain from breastfeeding [26,27]. According to Victoria et al, 823,000 deaths in children younger than the age of 5 and up to 20,000 deaths from breast cancer can be prevented each year only by scaling up the level of breastfeeding to a nearuniversal level [30].…”
Section: Discussionmentioning
confidence: 66%
“…Murphy et al conducted a study to investigate the impact of exclusive breastfeeding for a minimum duration of 90 days and the incidence of illness in infants. The findings indicated that breastfeeding for 90 days and more was associated with a significant decrease in the likelihood of being admitted to the hospital, the number of nights spent in the hospital, and also the proneness for developing respiratory diseases such as chest infections, asthma, and common colds [27]. Furthermore, many studies emphasize the role of breastfeeding in the immune development of the infant since the primary milk produced by the mother is rich in immunologically active molecules and various other key nutrients and vitamins [26].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that breastfeeding may improve immune function, thereby providing short- and long-term protection to offspring against infection and allergies. 38 , 39 A prospective cohort study reported that infants who were breastfed were less likely to develop asthma 40 and other childhood morbidities, demonstrating the substantial health and economic implications of breastfeeding. But Lodge 38 found a limited association between breastfeeding and a reduced risk of AR and eczema in the first 2 or 5 years of life, which were the same as our findings.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study was recently conducted in Ireland by Murphy, S., Carter, L., Al Shizawi, T. et al Their study researched the correlation between 90 days of exclusive breastfeeding and the incidence of different diseases in Irish children. The investigation showed that children exclusively breastfed for 90 days had a lower probability of developing respiratory infections or asthma [15].…”
Section: Effects On Respiratory Infectionsmentioning
confidence: 95%
“…Notably, German and Romanian infants were exclusively breastfed for the rst six months of age at notably higher rates than the global average during 2007-2014, as determined by the World Health Organization in 2015 [15]. This is a positive indication of the growing recognition of the bene ts of human milk and the importance of exclusive breastfeeding during the rst six months of life.…”
Section: Opinions and Attitude On Breastfeedingmentioning
confidence: 99%